Oral health management of 97 patients living with HIV/AIDS in Ribeirão Preto, São Paulo, Brazil - Danieli Cristina da SILVA; Alan Grupioni LOURENÇO; Ana Elisa Rodrigues Alves RIBEIRO; Alcyone Artioli MACHADO; Marilena Chinali KOMESU; Ana Carolina Fragoso MOTTA (Brazilian Oral Research, 2015)
Considering the changes antiretroviral therapy (ART) has brought to the treatment of HIV infection, the current clinical and laboratory profiles of HIV/AIDS individuals referred to oral health centers are crucially important in instructing dentists about the oral health management of these patients. The aim of the present study was to determine the clinical and laboratory profiles of HIV-infected individuals referred to a clinic for patients with special needs between 2005 and 2012 by retrospectively analyzing their dental records. A total of 97 records of HIV patients referred to the School of Dentistry of Ribeirão Preto, Universidade de São Paulo - USP, were analyzed. The Mann-Whitney test was used to determine the associations between mean CD4+ counts, mean viral load, and the presence of HIV-related oral lesions (HIV-OL). Most of the patients were male, and their mean age was 38.3 years. Eighty-nine (92%) patients were on regular ART, 77 (79.4%) had a CD4+ count higher than 200 cells/mm3, and 63 (64.9%) had an undetectable viral load. Twenty patients (20.6%) presented with some HIV-OL, including pseudomembranous and/or erythematous candidiasis and angular cheilitis, which were correlated with a low CD4+ count and with an undetectable viral load (p < 0.05). Among the branches of dentistry, periodontics, followed by surgery and restorative dentistry, was the most sought-after specialty, and no intercurrent events were observed during the dental treatment. It may be concluded that there are no restrictions on the dental treatment of patients on regular ART, It is important, though, that the treatment be based on local characteristics and on the prevention of oral diseases.